2016
DOI: 10.3390/ijms17060878
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31 Emerges as a Predictive Biomarker of Pathological Response and Outcome in Locally Advanced Rectal Cancer

Abstract: Neoadjuvant chemoradiotherapy (CRT) followed by total mesorectal excision has emerged as the standard treatment for locally advanced rectal cancer (LARC) patients. However, many cases do not respond to neoadjuvant CRT, suffering unnecessary toxicities and surgery delays. Thus, identification of predictive biomarkers for neoadjuvant CRT is a current clinical need. In the present study, microRNA-31 expression was measured in formalin-fixed paraffin-embedded (FFPE) biopsies from 78 patients diagnosed with LARC wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Though with a higher rate of microsatellite instability (MSI) in MC, the predictive value of MSI in response to radiotherapy is still controversial272829. Expression of high-mobility group box 1, Paf15 and several microRNAs had been reported to be associated with response to chemoradiotherapy3031323334. Unfortunately, neither lymph node dissemination nor molecular phenotype status had been recorded in our study and these analyses could not be performed.…”
Section: Discussionmentioning
confidence: 80%
“…Though with a higher rate of microsatellite instability (MSI) in MC, the predictive value of MSI in response to radiotherapy is still controversial272829. Expression of high-mobility group box 1, Paf15 and several microRNAs had been reported to be associated with response to chemoradiotherapy3031323334. Unfortunately, neither lymph node dissemination nor molecular phenotype status had been recorded in our study and these analyses could not be performed.…”
Section: Discussionmentioning
confidence: 80%
“…However, in CRC cells, LOC554202 has a tumor suppressor role in the activation of specific caspase cleavage cascades, and low expression of LOC554202 was associated with advanced pathologic stage and increased tumor size (32). miR-31 is a widely investigated miRNA and studies have reported controversial conclusions regarding its role in CRC cells (52)(53)(54)(55)(56). These studies suggest that a high expression of this miRNA in cancer does not always result in a decreased tumor growth, including that noted in cases of the oncosuppressors p53 and phosphatase and tensin homolog.…”
Section: Os ---------------------------------------------------------mentioning
confidence: 99%
“…The implication of the well-known oncomiR-21 also in prediction of response to preoperative CRT has been confirmed in seventy FFPE tumor tissues of LARC patients who underwent to CRT thanks to the work of Caramés et al [ 65 ]. Subsequently, the same authors identified another predictive miRNA biomarker, namely miR-31 [ 66 ]. Differently from a previously published study, in this work miR-31 overexpression correlated with an unfavorable response to nCRT and OS in LARC patients [ 64 , 66 ].…”
Section: Micrornas In Locally Advanced Rectal Cancermentioning
confidence: 99%
“…Subsequently, the same authors identified another predictive miRNA biomarker, namely miR-31 [ 66 ]. Differently from a previously published study, in this work miR-31 overexpression correlated with an unfavorable response to nCRT and OS in LARC patients [ 64 , 66 ].…”
Section: Micrornas In Locally Advanced Rectal Cancermentioning
confidence: 99%